Optical switching in glass fibre composite. (August 2022) - Holmes, Christopher; Godfrey, Mike; Mennea, Paolo L.; Bull, Daniel J.; Dulieu-Barton, Janice
Highlights: Optical switch embedded within advanced laminated composite. Switching achieved through silica planar optics within glass fibre reinforced polymer. Physically machined Flame Hydrolysis Deposition planar integrated optics. Flexible planar photonics. 2π optical switching of a Mach Zehnder interferometer through Ohmic heating. Abstract: We demonstrate for the first time the reconfigurability of optical signals within advanced laminated composite. The approach employs an ultra-thin planar optical circuit, embedded within glass fibre reinforced polymer (GFRP) that switches an optical input though Ohmic heating. This advance highlights new opportunities for optical reconfigurability within advanced composites, enabling data transmission redundancy and a consideration of branching optical fibre architectures.